Pengembangan Sistem Penyulingan Bahan Bakar Bioetanol dari Sampah Organik Pertanian di Desa Sempajaya, Kecamatan Berastagi, Kabupaten Karo: Indonesia - Sidabutar, Rivaldi; Trisakti, Bambang; Irvan, Irvan; Hanum, Farida; Surya, Indra; Taslim, Taslim; Sinaga, Mersi Suriani; Rizky, Muhammad Rafly; Sitepu, Lusti Angelica; Juniansyah, Muhammad Fadhillah; Abdurrahman, Muhammad Faiz; Syafutra, Wahyu Pramudya; Marbun, Daniel S (UII, 2026)
Unsold vegetable waste from agricultural products generally rots and ends up in landfills, increasing waste volume and creating environmental problems. Utilizing vegetable waste as a raw material for bioethanol is a potential alternative, considering that bioethanol is a renewable energy source that can be produced through a biomass fermentation process. This study designed a 15 liter bioethanol production unit utilizing various types of vegetable waste, such as potatoes, pineapples, carrots, mustard greens, and cabbage. The process unit consists of pre-treatment equipment (a pre-cooking tank, a crusher, and a pressure tank), a fermenter equipped with two 30 cm diameter paddle-type manual stirrers, and a stainless steel distillation unit equipped with a heater and cooling tank. The fermentation process lasts for 48–72 hours and produces bioethanol with a concentration of 45%. This program is expected to provide dual benefits: as a solution for vegetable waste management to reduce environmental impacts and as a source of additional income for the community through the utilization of the bioethanol produced.